Trapping field assisted backscattering in strong-field photoemission from dielectric nanospheres - Seiffert, Lennart; Henning, Philipp; Rupp, Philipp; Zherebtsov, Sergey; Hommelhoff, Peter; Kling, Matthias Friedrich; Fennel, Thomas (Journal of Modern Optics, 2017)
We study strong-field ionization of dielectric nanospheres and focus on the enhancement of the cut-off energies for backscattering electrons resulting from charge interaction. Though recent studies clearly demonstrated the decisive impact of a surface trapping field on the electron backscattering process, a clear picture of the underlying mechanism is lacking. Here, we provide this picture and present a simple and transparent extension of the famous three-step model of strong-field science by adding a triangular surface trapping potential. We justify this model for the case of dielectric nanospheres based on high-level transport simulations. The analysis of the trapping field assisted backscattering provides a universal scaling of the maximal recollision and backscattering energies as 9 Up and 14.5 Up, respectively, where Up the local ponderomotive potential. The universal nature of the enhancement over the conventional three-step model is of particular interest for the generation of attosecond electron bunches via near-field induced photoemission and high harmonic generation at nanostructures.
UnivIS-Import:2017-12-18:Pub.2017.nat.dphy.IAP.exphys.trappi
Keywords: Strong-field ionization; electron backscattering; nanostructures; near-fields; dielectric nanospheres